Holistic approach to understanding behaviour of 5-12 year olds in a social environment - Lieģeniece, Daina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The primary purpose of this study was to become acquainted with theoretical background of the investigations of the phenomenon “self-regulation”. It was done by analysing various sources of information, receiving cues from SAGE publication data bases (after 1990). The idea of analyses was assumed by taking into consideration D.Lieģeniece’s (1997, 1999) elaborated model “Holistic approach to education of a 5-7 year old child”. Holistic approach model identifies child’s self-regulation as a construct influenced by a whole personality: cognitive processes, emotionality, volitional sphere, needs, motives etc. This work is reviewed as research on characteristics of children’s self-regulation as a point of children’s school-related competence across the preschool and elementary school. In the current study three aspects are considered, influencing self-regulation ability (1) emotionrelated self-regulation ability (2) cognitive competence (3) situation knowledge and social skills. Research suggests taking into consideration dynamic influences among intrinsic factors causing children’s behaviour.